Measuring Entrepreneurial Success in Inclusive Contexts in African countries: Indicators and Evaluation Frameworks - Kounouwewa, Jules; Chao, Deng (International Review of Management and Marketing, 2026)
Entrepreneurial success has traditionally been evaluated using economic indicators such as profitability, firm growth, and survival rates. However, in African contexts where inclusive entrepreneurship plays a critical role in promoting equity and sustainable development, such conventional measures often overlook essential dimensions of inclusion, empowerment, and social transformation. This study develops a multidimensional framework for measuring entrepreneurial success in inclusive contexts across selected African countries. It integrates financial, human, social, and institutional dimensions to capture the real impact of entrepreneurship on marginalized and underrepresented groups, including women, youth, and persons with disabilities. Using a mixed-method design, the study draws on cross-country data from the Global Entrepreneurship Monitor (GEM), African Development Bank (AfDB) SME databases, and national enterprise surveys conducted between 2020 and 2024. Four econometric models are estimated to test the relationships between financial inclusion, human capital development, institutional support, and social empowerment as determinants of entrepreneurial success. The models include: (1) a financial inclusion model assessing access to credit and financial services; (2) a human capital model examining training, education, and experience; (3) an institutional support model focusing on public policy, incubator networks, and digital infrastructure; and (4) an integrated multidimensional model combining all key drivers. The results demonstrate that inclusive entrepreneurial success is significantly influenced by access to financial services, supportive institutional environments, and the availability of digital tools that enhance market participation. Moreover, the study introduces an Inclusive Entrepreneurial Success Index (IESI)-a composite measure designed to evaluate the performance of entrepreneurs within inclusive ecosystems. The IESI allows for comparative analysis across regions and policy programs, providing an adaptable tool for researchers, policymakers, and development practitioners. The findings emphasize the need to move beyond profit-based evaluation models toward broader indicators that reflect empowerment, equality of opportunity, and social impact. This new framework contributes to inclusive entrepreneurship theory and offers strategic insights for designing equitable and sustainable entrepreneurship policies aligned with the African Union’s Agenda 2063 and the UN Sustainable Development Goals (SDGs).